Perioperative Mortality in Nonelderly Adult Patients With Cancer: A Population-based Study Evaluating Health Care Disparities in the United States According to Insurance Status. (May 2018) - Amini, Arya; Yeh, Norman; Jones, Bernard L.; Bedrick, Edward; Vinogradskiy, Yevgeniy; Rusthoven, Chad G.; Amini, Ava; Purcell, William T.; Karam, Sana D.; Kavanagh, Brian D.; Guntupalli, Saketh R.; Fisher, Christine M.
Abstract : Objectives: The purpose of this study was to evaluate whether insurance status predicts for perioperative mortality (death within 30 d of cancer-directed surgery) for the 20 most common surgically treated cancers. Methods: The SEER database was examined for the 20 most common surgically resected cancers and included nonelderly adults, aged 18 to 64 years. The database was queried from 2007 to 2011, with a total of 506, 722 patients included in the analysis. Results: Insurance status for all patients were the following: non-Medicaid insurance (83%), any Medicaid (10%), uninsured (4%), and unknown (3%). In univariate analyses, predictors for perioperative mortality included insurance status ( P <0.001), age ( P =0.015), race ( P <0.001), marital status ( P <0.001), residence ( P =0.002), percent of county below the federal poverty level ( P <0.001), and median county-level income ( P <0.001). Perioperative mortality was also associated with advanced disease ( P <0.001). Under multivariate analysis, patients with either Medicaid (Cochran-Mantel-Haenszel odds ratio [CMH OR], 1.21; 95% confidence interval [CI], 1.14-1.29; P <0.001) or uninsured status (CMH OR, 1.56; 95% CI, 1.44-1.70; P <0.001) were more likely to die within 30 days of surgery compared with patients with non-Medicaid insurance. When comparing Medicaid with the uninsured, Medicaid patients had significantly lower rates of perioperative mortality when compared with the uninsured (CMH OR, 0.80; 95% CI, 0.73-0.89, P <0.001). Conclusions and Relevance: In the largest reported analysis of perioperative mortality evaluating the 20 most common surgically treated malignancies, patients with Medicaid coverage or without health insurance were more likely to die within 30 days of surgery, with the uninsured having the worst outcomes.